Competitiveness and export development strategy for Indonesia's creative economy sector in the ASEAN market - Haryadi Haryadi; Etik Umiyati; Sony Tian Dhora (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
The main objectives of this study are (1) to analyze the competitiveness of Indonesian exports in the ASEAN market (2) to formulate a strategy that will be able to support the export competitiveness of Indonesia's creative economy. Revealed Comparative Advantage, Acceleration Ratio, Export Competitiveness Index, and SWOT analysis (to determine a creative economy export development strategy using quantitative) were used as analysis tools. This study focused on examining the subsectors of architecture, movies, animation and video, craft, culinary, music, fashion, publishing, and art. Based on the results, we conclude that all subsectors have export competitiveness in the ASEAN market. Among them, craft and culinary appear as subsectors with strong competitiveness and meet all the analysis criteria. The results also show that SO strategy (growth) could be chosen to develop the creative economy.